2011
DOI: 10.1007/s11065-011-9167-9
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Spectrum Disorders: Neuropsychological and Behavioral Features

Abstract: Heavy prenatal alcohol exposure can cause alterations to the developing brain. The resulting neurobehavioral deficits seen following this exposure are wide-ranging and potentially devastating and, therefore, are of significant concern to individuals, families, communities, and society. These effects occur on a continuum, and qualitatively similar neuropsychological and behavioral features are seen across the spectrum of effect. The term fetal alcohol spectrum disorders (FASD) has been used to emphasize the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
544
1
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(573 citation statements)
references
References 212 publications
(330 reference statements)
20
544
1
8
Order By: Relevance
“…Visual-motor impairments and greater difficulty performing complex tasks are challenges that have also been found in other studies of children with FASD (Kodituwakku, 2007(Kodituwakku, , 2009Mattson, Crocker, & Nguyen, 2011). Additionally, our findings are congruent with results from a study that examined the relationship between sensorimotor skills, visual-motor integration, and handwriting in a diverse sample of children with learning or behavioral disabilities or both (Klein, Guiltner, Sollereder, & Cui, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Visual-motor impairments and greater difficulty performing complex tasks are challenges that have also been found in other studies of children with FASD (Kodituwakku, 2007(Kodituwakku, , 2009Mattson, Crocker, & Nguyen, 2011). Additionally, our findings are congruent with results from a study that examined the relationship between sensorimotor skills, visual-motor integration, and handwriting in a diverse sample of children with learning or behavioral disabilities or both (Klein, Guiltner, Sollereder, & Cui, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Consistently, researchers looking at clinical and community samples, as well as caregivers, have found that individuals prenatally exposed to alcohol may have significant neurobehavioral impairments. In particular, deficits are reported in executive functioning (Rasmussen, 2005), learning, memory, language, intelligence, motor, visual-spatial abilities (see Kodituwakku, 2007Kodituwakku, , 2009Mattson, Crocker, & Nguyen, 2011), and academic achievement (Streissguth et al, 1994). Problems with disrupted school experiences, mental health problems, incarceration and retention in the justice system, as well as inappropriate sexual behaviors and alcohol and drug abuse have also been described (Streissguth, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…25,26 However, research has yet to delineate a specific neurobehavioral profile or core symptoms of FASD. 1 Given the variable effects of dose, timing and pattern of alcohol use during pregnancy, 27 in conjunction with varying stages of CNS development, the identification of a central neurobehavioral profile common to all patients with FASD is formidable. Since the third edition of the manual, DSM has adopted an approach based on descriptive, observable symptomology.…”
Section: Discussionmentioning
confidence: 99%
“…17 Current FASD diagnostic practices are multifaceted and complex, with the use of multidisciplinary teams being considered best practice. 1 Although this approach results in comprehensive assessment, it is costly and limits clinical capacity. 2 The development of more efficient diagnostic systems is needed to identify a wider range of patients affected by prenatal alcohol exposure and to improve access to services.…”
mentioning
confidence: 99%